Pediatric Malignant Arrhythmias Caused by Rare Homozygous Genetic Variants in TRDN: A Comprehensive Interpretation - Sarquella-Brugada, Georgia; Fernandez-Falgueras, Anna; Cesar, Sergi; Arbelo, Elena; Jordà, Paloma; García-Álvarez, Ana; Cruzalegui, Jose Carlos; Merchan, Erika Fernanda; Fiol, Victoria; Brugada, Josep; Brugada, Ramon; Campuzano, Oscar (Frontiers in Pediatrics, 2021)
Aim: To perform a comprehensive phenotype-genotype correlation of all rare variants in Triadin leading to malignant arrhythmias in pediatrics. Methods: Triadin knockout syndrome is a rare entity reported in pediatric population. This syndrome is caused by rare variants in the TRDN gene. Malignant ventricular arrhythmias and sudden cardiac death can be a primary manifestation of disease. Although pharmacological measures are effective, some patients require an implantable defibrillator due to high risk of arrhythmogenic episodes. Main Results: Fourteen rare genetic alterations in TRDN have been reported to date. All of these potentially pathogenic alterations are located in a specific area of TRDN, highlighting this hot spot as an arrhythmogenic gene region. Conclusions: Early recognition and comprehensive interpretation of alterations in Triadin are crucial to adopt preventive measures and avoid malignant arrhythmogenic episodes in pediatric population.